2018
DOI: 10.1093/eurheartj/ehy625
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diabetes mellitus on the clinical phenotype of hypertrophic cardiomyopathy

Abstract: Aims Diabetes mellitus (DM) aggravates the clinical features of ischaemic and hypertensive heart diseases and worsens the prognosis of heart failure patients. Hypertrophic cardiomyopathy (HCM) and diabetes coexist fairly frequently in elderly patients but the impact of DM on the clinical phenotype of HCM is yet unknown. We sought to describe if predominant features of heart failure in DM patients exist independently in HCM. Methods and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 33 publications
6
28
2
3
Order By: Relevance
“…In the present study, LGE positive patients had a trend towards a higher prevalence of diabetes mellitus than in LGE negative patients. The presence of diabetes may have an impact on the features of HCM because of diabetes is correlated with higher degrees of diastolic dysfunction 37 . In addition, LGE negative patients had the highest heart rate among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, LGE positive patients had a trend towards a higher prevalence of diabetes mellitus than in LGE negative patients. The presence of diabetes may have an impact on the features of HCM because of diabetes is correlated with higher degrees of diastolic dysfunction 37 . In addition, LGE negative patients had the highest heart rate among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study reported the impact of DM on the clinical phenotype of HCM [3]. They showed that HCM patients with diabetes have a higher cardiovascular risk profile, a lower functional capacity, and more heart failure symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is highly common among patients with cardiovascular disease and is associated with increased burden of morbidity and hospitalization [3]. The functional changes occurring in DM can significantly alter the hemodynamic stress on the heart.…”
Section: Introductionmentioning
confidence: 99%
“…HCM is predominantly caused by mutations in sarcomeric protein-encoding genes, most frequently in myosin binding protein C3 (MYBPC3) or -myosin heavy chain 7 (MYH7) (1)(2)(3)(4)(5). Notably, 30 to 40% of patients with HCM are negative for sarcomeric genes and exhibit HCM with unknown causes (1)(2)(3)(4). Recent emerging evidence suggests that ~10% of HCM cases coexist with diabetes mellitus in the absence of hypertension and obesity (3).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, 30 to 40% of patients with HCM are negative for sarcomeric genes and exhibit HCM with unknown causes (1)(2)(3)(4). Recent emerging evidence suggests that ~10% of HCM cases coexist with diabetes mellitus in the absence of hypertension and obesity (3).…”
Section: Introductionmentioning
confidence: 99%